A Conceptual Framework for Antecedents and Consequence of Organizational Learning Capability - Hashim, Azharuddin (Information Management and Business Review, 2013)
In extension of organizational learning study, the concept of organizational learning capability had emerged which stress on the importance of the facilitating factors for organizational learning or the organizational propensity to learn. Despite its recognized importance in the literature, little research has been devoted to the research centered on the related factors that could contribute to its development. Factors such as human resource management practices and leadership are identified as the strong predictor of organizational learning. There are also little attention has been given to relate organizational learning with organizational commitment, thus more research is required to analyze the relationships between organizational learning and issues concerning employees, such as organizational commitment. Thus this paper proposed the integration of human resource management practices, servant leadership, organizational learning capability and organizational commitment in a conceptual framework for future research.